Assessment of biogenic silica potential for biomedical applications - Navarro, Francisco Ezequiel (2024)
Diatoms are eukaryotic microalgae, which present a cell wall made of amorphous silica called frustule. Studies in micro/nano-technology show that frustules are potential materials for various applications, such as drug delivery, biosensors, and rapid bleeding control. The aim of this study was to evaluate the physicochemical properties and blood tissue biocompatibility of frustules extracted from Halamphora coffeaeformis, a diatom native from Bahía Blanca Estuary, to assess their potential application in biomedical fields. Frustules were obtained from two different culture methods: photobioreactor (F-PBR) and open raceway pond (F-RAC). Both cultures underwent an oxidation treatment with hydrogen peroxide at 80ºC for 12h. Afterwards, the frustules were subjected to three calcination treatments at 300ºC, 500ºC, and 800ºC, based on mass loss and stabilization identified through thermogravimetric analysis. Significant changes were observed in the composition and surface properties of the frustules after the treatments. In general, the percentages of Si and O tended to increase as temperatures rose, while C content decreased. This trend corresponded with a reduction in C=O and C-H groups at higher temperatures. BET surface area values were highest at 300ºC for both cultivation methods, with F-RAC (68.6 m²/g) significantly surpassing F-PBR (27 m²/g). Additionally, z-potential measurements indicated higher stability for F-PBR (-33 mV) compared to F-RAC (-20 mV), suggesting better dispersion stability in an aqueous medium and fewer aggregates. The preliminary hemocompatibility study, displayed by evaluation of hemolysis and osmotic fragility on red blood cells, showed biocompatibility of frustules with erythrocytes. In conclusion, H. coffeaeformis frustules, particularly those from photobioreactor cultivation and calcined at 300ºC, possess favorable physicochemical properties and biocompatibility with blood tissue. These characteristics highlight their potential as drug carriers.